EFEK MEDIASI KINERJA PERUSAHAAN TERHADAP HUBUNGAN STRUKTUR MODAL DENGAN NILAI PERUSAHAAN PADA PERUSAHAAN CONSUMER NON CYCLICAL - Meirisa, Faradila (MOTIVASI, 2024)
Purpose– This Study determining investment decisions, investors need to consider the company value which describes the welfare provided by the company. The aim of this research is to prove whether company performance mediates the relationship between capital structure and company valueDesign/methodology– The type of research used is descriptive research and associative research. The analysis technique used is PLS-SEM (Partial Least Square) analysis with a research sample of 75 non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) in 2020-2023.Findings - The results of this research show that capital structure influences company value and company performance. Company value is partially influenced by company performance. Simultaneously, capital structure and company performance have a significant effect on company value. The research results prove that the influence of capital structure on company value can be mediated by company performance.